The Effects of An Empowerment Program on The Self-Control of Amphetamine Use Disorder Patients - เผือกผ่อง, กชพร; บรรทุมพร, นุชนาถ; สมประเสริฐ, ชมชื่น (Journal of The Royal Thai Army Nurses, 2019)
The purpose of this quasi-experimental study was to examine the effects of an empowerment program on amphetamine use disorder patients. The sample consisted of 60 males aged between 20-59 years in the Princess Mother National Institute for Drug Abuse Treatment (PMNIDAT) in Thailand. They were randomly assigned to either the experimental or control group (n = 30 in each group). The experimental group received the empowerment program for 5 weeks, 90-120 minutes per session, twice a week consecutively. The participants in the control group received routine care from the ward. Personal information forms were used to collect the data. The participants’ self-control scores were measured using a self-control schedule developed from Rosenbaum’s self-control schedule before and after the empowerment program. Descriptive statistics were used to represent the personal information about the participants; a dependent t-test was used to compare the mean of the self-control scores before and after the intervention in with each group; and an independent t-test was used to examine the mean differences in the self-control scores between the experimental and control groups. The study found that 1) after receiving the empowerment program, there was a significant increase in the mean of the self-control scores (M = 169.40, SD = 18.16) (t = 8.18, p<.001) and 2) there was a significant difference in the mean differences in the self-control scores in the experimental group ( = 10.33, SD = 6.92) and control group ( = 1.83, SD = 7.43) between the pretest and posttest interventions for both groups (t = 4.58, p<.001). The findings suggest the beneficial effects of such an empowerment program in increasing the self-control of amphetamine use disorder patients in terms of rehabilitation.